Hospitalisation rates for children with intellectual disability or autism born in Western Australia 1983–1999: a population-based cohort study. Issue 2 (27th February 2013) - Bebbington, Ami; Glasson, Emma; Bourke, Jenny; de Klerk, Nicholas; Leonard, Helen
Abstract : Objectives: To describe the hospitalisation patterns in children with intellectual disability (ID) and/or autism spectrum disorder (ASD) after the first year of life and compare with those unaffected. Design: Prospective cohort study using data linkage between health, ID and hospitalisation population-based datasets. Setting: Western Australia. Participants: 416 611 individuals born between 1983 and 1999 involving 1 027 962 hospital admission records. Five case categories were defined (mild/moderate ID, severe ID, biomedically caused ID, ASD with ID and ASD without ID) and compared with the remainder of children and young people. Primary and secondary outcome measures: Time to event analysis was used to compare time hospitalisation and rate of hospitalisation between the different case-groups by estimating HR, accounting for birth year and preterm birth status. Results: ID and/or ASD were found to be associated with an increased risk of hospitalisation compared with the remainder of the population. The increase in risk was highest in those with severe ID and no ASD (HR=10.33, 95% CI 8.66 to 12.31). For those with ID of known biomedical cause or mild ID of unknown cause, the risk of hospitalisation was lower (HR=7.36, 95% CI 6.73 to 8.07 and HR=3.08, 95% CI 2.78 to 3.40, respectively). Those with ASDs had slightly increased risk (HR=2.82, 95% CI 2.26 to 3.50 for those with ID and HR=2.09, 95% CI 1.85 to 2.36 for those without ID). Conclusions: Children with an ID or ASD experience an increased risk of hospitalisation after the first year of life which varied from 2 to 10 times that of the rest of the population. Findings can inform service planning or resource allocation for these children with special needs.